Base Axioms of Modular Supermatroids - Xiaonan Li; Sanyang Liu (Journal of Applied Mathematics)
This paper studies axiom systems of supermatroids. Barnabei et al.'s base axioms concerning poset matroids (i.e., distributive supermatroids) are generalized to modular supermatroids, and a mistake in the proof of base axioms of poset matroids is pointed out.